AB0603 The effects of technetium [99TC] methylenediphosphonate on peripheral gammadelta T cells and regulatory T cells in patients with rheumatoid arthritis. (23rd January 2014) - Su, D.; Li, X.; Sun, L.
Abstract : Background: Regulatory T-cells (Tregs) are the guardians of peripheral tolerance acting to prevent autoimmune diseases such as rheumatoid arthritis (RA). Defects in Tregs have been reported in RA, and the application of therapeutic drugs may cause enhancement of Treg numbers, which is positively correlated with clinical remission of disease. γδT cells display characteristics of both innate and adaptive immunity and play important roles in infectious diseases and tumor, but exert pro- or anti-inflammatory effects depending on various local milieu. Studies have shown that γδT cells could exert immuno-regulatory effect by secreting IL-10 and TGF-β, participating in the pathogenesis of autoimmune diseases. Objectives: To investigate the changes of γδT cell and Treg percentage as well as secretion of associated inflammatory cytokines in RA patients after the treatment with Technetium [99Tc] methylenediphosphonate injection(99Tc-MDP) Methods: Active RA patients were treated with 99Tc-MDP for 14 days. Before and after treatment, the percentages of peripheral blood γδT cells and Treg were detected by flow cytometry (FACS), and serum levels of IL-10, IFN-γ, TNF-α were measured using enzyme-linked immunosorbent assay (ELISA). DAS28 scores before and after treatment were also recorded and correlation analysis was performed. Results: The percentages of peripheral blood γδT cells and Treg in RA patients presented no significant difference with healthy controls. After treatment with 99Tc-MDP, the frequency of γδT cells and Treg in the peripheral blood of RA patients were significantly elevated, meanwhile with markedly increased serum level of IL-10 and significantly decreased serum levels of INF-γ and TNF-α levels. The changes of γδT cells and Treg percentages and serum levels of cytokines were positively correlated with DAS28 score. Conclusions: The bisphosphonate 99Tc-MDP may exert its anti-inflammatory effect on RA patients by up-regulation of the frequency of peripheral γδT cells and Treg as well as increased secretion of IL-10. Disclosure of Interest: None Declared